Far‐Red and Near‐Infrared Boron Schiff Bases (BOSCHIBAs) Dyes Bearing Anionic Boron Clusters. Issue 21 (17th May 2021) - Corona‐López, María M.; Muñoz‐Flores, Blanca M.; Chaari, Mahdi; Nuñez, Rosario; Jiménez‐Pérez, Víctor M.
Abstract: Here, we report a short series of six new boron Schiff bases (BOSCHIBAs), four of them bearing anionic boron clusters. The boron complexes (1 –2 ) were synthesized by the multicomponent reaction. The Boron Schiff bases were appropriately functionalized with boron cluster anions [B12 H12 ] 2− (3 –4 ) and [3, 3'‐Co(C2 B9 H11 )2 ] − (5 –6 ). Remarkably, BOSCHIBAs bearing [B12 H12 ] 2− showed fluorescence emission to the NIR and far‐red regions (3 : 747 nm, 4 : 690 nm), while 5 and 6 exhibited emission in the UV region (5 : 525 and 6 : 475 nm). Notably, complexes 2, 5, and 6 showed the highest photostability, followed by the boron complexes 1 and 3, which suggest that the nature of the boron cluster influences photostability properties. Compounds 3 –4 represent the first example of boron Schiff bases bearing boron cluster anions [B12 H12 ] 2− exhibiting fluorescence emission in the NIR and far‐red regions, make them potential candidates as fluorescence probes for bioimaging. Abstract : New boron Schiff bases (BOSCHIBAs) were functionalized with boron cluster anions [B12 H12 ] 2− (3 –4 ) and [3, 3'‐Co(C2 B9 H11 )2 ] − (5 –6 ). Remarkably, BOSCHIBAs bearing [B12 H12 ] 2− showed fluorescence emission to the NIR and far‐red regions (3 : 747 nm, 4 : 690 nm). Compounds 3 and 4 represent the first example of boron Schiff bases bearing boron cluster anions [B12 H12 ] 2− exhibiting fluorescence emission in the NIR and far‐red regions, make them potential candidates as fluorescence probes for bioimaging.